2017
DOI: 10.18235/0000602
|View full text |Cite
|
Sign up to set email alerts
|

Are Oil and Gas Smothering the Private Sector in Trinidad and Tobago?

Abstract: ative Commons IGO 3.0 Attribution-NonCommercial-NoDerivatives (CC-IGO BY-NC-ND 3.0 IGO) license (http://creativecommons.org/licenses/by-nc-nd/3.0/igo/legalcode) and may be reproduced with attribution to the IDB and for any non-commercial purpose.No derivative work is allowed.Any dispute related to the use of the works of the IDB that cannot be settled amicably shall be submitted to arbitration pursuant to the UNCITRAL rules. The use of the IDB's name for any purpose other than for attribution, and the use of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…In the mainstream literature, resource-curse proponents argue that resource wealth and endowments are correlated with poor economic growth (Auty, 2002; Sachs & Warner, 1995). In resource-dependent developing countries, according to these scholars, manufacturing growth has stagnated due to the leakage of economic resources to enclave commodity-based sectors that produce little employment, appreciate the exchange rate and absorb a considerable amount of foreign exchange (Frankel, 2012; Khadan, 2016). Perverse effects are supposedly spread through poor inherited economic institutions such as weak property rights and contracting, and such countries are ultimately plagued by relatively low per capita incomes, price distortions due to state intervention and poor human development outcomes (Acemoglu, Johnson, & Robinson, 2001; Engerman & Sokoloff, 2005; Krueger, 1974; Sachs & Warner, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the mainstream literature, resource-curse proponents argue that resource wealth and endowments are correlated with poor economic growth (Auty, 2002; Sachs & Warner, 1995). In resource-dependent developing countries, according to these scholars, manufacturing growth has stagnated due to the leakage of economic resources to enclave commodity-based sectors that produce little employment, appreciate the exchange rate and absorb a considerable amount of foreign exchange (Frankel, 2012; Khadan, 2016). Perverse effects are supposedly spread through poor inherited economic institutions such as weak property rights and contracting, and such countries are ultimately plagued by relatively low per capita incomes, price distortions due to state intervention and poor human development outcomes (Acemoglu, Johnson, & Robinson, 2001; Engerman & Sokoloff, 2005; Krueger, 1974; Sachs & Warner, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the case of Trinidad and Tobago (hereafter T&T), recent studies have suggested that reliance on petroleum and gas resources have weakened manufacturing growth and diminished innovation (Artana, Auguste, Ramiro, Sookram, & Watson, 2007; Khadan, 2016). Critics challenge these conclusions by invoking the agential role that the organized labor played in the country’s governance and human development (Edwards, 2017a, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Trinidad and Tobago (T&T) is considered a small highly open hydrocarbon exporting economy and as such the non-energy export sector has been a key area of policy focus over the last few decades especially in terms of articulating pathways for export diversification. In the context of the economic adjustments associated with the global pandemic, the paper posits that the economy is poised to leverage the opportunity for reset from a policy perspective and to reconsider strategies to expand the non-energy sector [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Against these realities T&T policy makers have recognized the importance of progressing the local and by extension the regional trade facilitation agenda as a strategy to improve competitiveness and in the context of economic diversification, increase exports [7,8]. To this end, this paper aims to focus the discussion on key trade facilitation variables which can have a marked improvement on trade costs and hence on the overall level of exports.…”
Section: Introductionmentioning
confidence: 99%
“…This is a particularly important policy issue as an "inadequately educated workforce" has been consistently identified by firms as the most important constraint to their performance (PROTEqIN Survey 2014;and World Bank Enterprise Survey 2010). The factors underlying this constraint have been attributed to worker emigration, low quality of education, inadequate training offered by local educational institutions, and skills shortages and mismatches (Khadan 2017;Mishra 2006).…”
Section: Introductionmentioning
confidence: 99%